Socioeconomic Reinvention and Expanding Engagement with Climate Change Policy in American Rust Belt Cities - Scott E. Kalafatis (Atmosphere, 2020)
Despite an appreciation for the role of cities in addressing global climate change, more studies are needed that explore how climate change policies relate to cities’ everyday governing concerns. Such insights are critical for understanding how climate change policy will expand, play out, and evolve as it moves from experimental efforts in particularly innovative cities to the majority of cities. This study addresses these needs using 32 interviews and over 200 survey responses from smaller cities (populations under 100,000) in the American rust belt. In the interviews comparing cities’ financial concerns, economic development considerations, and how other cities influence them, a distinctive mindset amongst cities highly engaged with climate change emerged. Highly engaged cities were those pursuing socioeconomic reinvention, informed by efforts to identify and apply policy ideas from a wide range of other cities across the United States and internationally. Results of the regression analyses supported the notion that financial concerns, economic development considerations, and the influence of other cities shape decisions about climate change policy in these cities. However, they also highlighted the complexity of these issues and that the role these factors had in shaping climate change policy will likely continue to evolve as these policies continue to diffuse to more places.